1999
DOI: 10.1098/rspb.1999.0684
|View full text |Cite
|
Sign up to set email alerts
|

The loss of organic nitrogen during marine primary production may be significantly overestimated when using 15N substrates

Abstract: Field studies indicate that natural phytoplankton populations may release very signi¢cant amounts (204 0%) of newly assimilated dissolved inorganic nitrogen (DIN) as dissolved organic nitrogen (DON). In laboratory cultures, however, it is usually possible to account for at least 90% of nitrogen added to the system as DIN plus cell nitrogen. Here we show that the bulk of the missing nitrogen may be accounted for as dissolved free and dissolved combined amino acids. In cultures (which usually have a biomass dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
1
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 39 publications
0
38
1
1
Order By: Relevance
“…it is likely that DCAA were produced during bacterial mineralization of riverine DON. In the Koiguste transect, the coincidence of maximum chl a concentrations and a minimum DCAA versus DON content at the outer station, 13 km from the shore, may support a low release of DCAA from growing algae as observed by Flynn & Berry (1999). The amount of phaeopigments also increased at the outer station (Table l ) , but the declining DCAA concentrations do not indicate that dead or inactive algae contributed DCAA to the water.…”
Section: -mentioning
confidence: 76%
See 1 more Smart Citation
“…it is likely that DCAA were produced during bacterial mineralization of riverine DON. In the Koiguste transect, the coincidence of maximum chl a concentrations and a minimum DCAA versus DON content at the outer station, 13 km from the shore, may support a low release of DCAA from growing algae as observed by Flynn & Berry (1999). The amount of phaeopigments also increased at the outer station (Table l ) , but the declining DCAA concentrations do not indicate that dead or inactive algae contributed DCAA to the water.…”
Section: -mentioning
confidence: 76%
“…In the present study, DCAA made up a major portion of DON, but the abundance of DCAA appeared not to correlate well with the biomass of living or dead phytoplankton. algae typically release a minor amount of DCAA Planktonic algae have been shown to produce DCAA (Flynn & Berry 1999). Another potential source of (Hellebust 1965, Ittekkot 1982 …”
Section: Fluxes Of Dissolved Nitrogen Compounds In the Gulf Of Rigamentioning
confidence: 99%
“…The higher release of DCAA in the light suggests that this release is a photosynthetically driven process, although Harlin and Craigie (1975) found no difference in light-dark DON release rates for a brown macroalgae. Phytoplankton may release 25-41% of DIN uptake as DON on short time scales (Bronk et al 1994) and much of this release may be DFAA and DCAA (Flynn and Berry 1999). Jorgensen (1982) found increased water column DFAA in the presence of U. lactuca, but based on the amino acid composition concluded that the DFAA were exudates from bacteria stimulated by algal DON release.…”
Section: Sediment Fluxes and The Influence Of Benthic Microalgaethe Dmentioning
confidence: 99%
“…On the contrary, nitrogen-replete cells are likely to release more organic nitrogen. Nitrogen release is related to nitrogen uptake by the phytoplankton (Bronk & Glibert 1993, Flynn & Berry 1999. Studies on the relationship between DON (dissolved organic nitrogen) release and the nitrogen states of algae will contribute to the clarification of phytoplankton dynamics and nitrogen cycling in aquatic environments.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%